1975
DOI: 10.1097/00000658-197507000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Bony Metastasis as the First Sign of Malignant Gastric Tumor or of Its Recurrence

Abstract: Symptomatic solitary bony metastasis as the First sign of asymptomatic gastric carcinoma is very infrequent. Only 8 cases reported by 7 authors have been found in the literature. Furthermore, solitary bony metastasis as the sole sign of recurrence after hopefully curative resections are so rare that none has been previously reported in the literature. Three additional instances of solitary and histologically proven osseous metastasis of malignant gastric neoplasms have been observed and treated at Memorial Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The least frequent metastatic sites were the shoulder girdle (17%), sacroiliac joint (7.2%), humerus (6.0%), sternum (4.2%) and the tibia (3.0%) (8), while to our knowledge, there is no previous report of the fibula as a site of bone metastasis in gastric adenocarcinoma. The predominance of metastatic disease in flat bones compared to the long bones is likely to be due to the presence of red marrow (4), supporting this fact that fibula as a long bone would be a rare site of metastasis as is the case in other cancers such as vaginal cancer, carcinoma of uterine cervix, lung cancer and colorectal cancer (9-13). On the other hand, as mentioned above, solitary bone metastasis as the sole sign of recurrence after hopefully curative resection without the disease spreading to other organs is much rarer (4).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The least frequent metastatic sites were the shoulder girdle (17%), sacroiliac joint (7.2%), humerus (6.0%), sternum (4.2%) and the tibia (3.0%) (8), while to our knowledge, there is no previous report of the fibula as a site of bone metastasis in gastric adenocarcinoma. The predominance of metastatic disease in flat bones compared to the long bones is likely to be due to the presence of red marrow (4), supporting this fact that fibula as a long bone would be a rare site of metastasis as is the case in other cancers such as vaginal cancer, carcinoma of uterine cervix, lung cancer and colorectal cancer (9-13). On the other hand, as mentioned above, solitary bone metastasis as the sole sign of recurrence after hopefully curative resection without the disease spreading to other organs is much rarer (4).…”
Section: Discussionmentioning
confidence: 93%
“…They also demonstrated that these extra-abdominal patterns of recurrence occurred rarely without evidence of intra-abdominal metastasis (5). Bone metastasis in gastric cancer is a rare condition and varies from 0 to 17.5 % (4), although Kobayashi. et al noted that this rate might be underestimated since bone scintigraphy is not performed as a routine clinical practice (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on resected tumors rendered a 1.2% incidence of osseous metastasis [3]. Metastases to the bone can occasionally be the first manifestation of the gastric tumor [4-6], but have only rarely been described as the sole manifestation of tumor recurrence [7,8]. We herein report a rather unusual case of synchronous bilateral femoral head metastases from gastric carcinoma 1 1/2 years after successful resection of the tumor without evidence of recurrence elsewhere.…”
Section: Introductionmentioning
confidence: 99%